2010
DOI: 10.1200/jop.200031
|View full text |Cite
|
Sign up to set email alerts
|

Capecitabine and Temozolomide: Design, Implementation, and Preliminary Outcomes From a Pilot Project to Ensure Safe Prescribing of Oral Chemotherapy

Abstract: Without adequate safety measures, oral chemotherapy can lead to undetected dosing errors. The Mayo Clinic launched a project to ensure that all capecitabine and temozolomide prescriptions receive an independent double check.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Pharmacy oversight is crucial for improving patient safety and providing optimal patient care, and previously published data have shown that pharmacist review of oral chemotherapy can improve error rates as well as increase the accuracy of oral chemotherapy orders. 5 As demonstrated in this study, clinical pharmacists provide valuable interventions by ensuring appropriate therapy, catching and correcting dosing errors before they reach the patient, coordinating patient care, and providing comprehensive chemotherapy education.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Pharmacy oversight is crucial for improving patient safety and providing optimal patient care, and previously published data have shown that pharmacist review of oral chemotherapy can improve error rates as well as increase the accuracy of oral chemotherapy orders. 5 As demonstrated in this study, clinical pharmacists provide valuable interventions by ensuring appropriate therapy, catching and correcting dosing errors before they reach the patient, coordinating patient care, and providing comprehensive chemotherapy education.…”
Section: Discussionmentioning
confidence: 92%
“…To date, few descriptions of other pharmacist-managed oral chemotherapy programs exist in the literature. 1,4,5 Furthermore, the programs that do exist describe limited use of EMRs. 1 Implementation of a pharmacist-managed oral chemotherapy program can improve both clinical and economic outcomes when caring for patients on these complicated medications, 1 and it is hypothesized that an electronic system for implementing such a program will provide an improved and more streamlined workflow that can translate into more meaningful pharmacy interventions.…”
Section: Introductionmentioning
confidence: 99%
“…24 Guidelines developed for physician practices or cancer center ambulatory facilities may not reach community pharmacies that are not affiliated with these practice sites, thus prescriptions must be double checked before they are dispensed to patients. 25 In addition, communication with community pharmacies that dispense TMZ should be enhanced. We encourage clinicians to report all errors that occur to accurately identify the true incidence.…”
Section: Resultsmentioning
confidence: 99%
“…Innovation is together a procedure and a result. It includes "production or adoption, assimilation, and exploitation of value-added novelty" [28], to produce outcomes such as new or improved products and services, or to create or improve production or management methods in organizations [29]. The definition of innovation has been broadened beyond the outputs of research and development or technology, to include assets with a knowledge base, social and enterprise innovation and business models, as previously defined by [30].…”
Section: Innovationmentioning
confidence: 99%
“…We have adopted a general management contingency framework for our current research, but this also applies to project management. A survey on the categorization framework for the project is in line with the contingency selection method, underlining the principle that "organizational structure must contribute to the context" [15,[21][22][23][25][26][27][28][29][30][31][32][33][34][36][37][38][39][40][41][42][43][44][45].…”
Section: Theoretical Foundationmentioning
confidence: 99%